Biomechanical behavior of valgus foot in children with cerebral palsy: A comparative study. Issue 12 (18th September 2015) - Guo, Junchao; Wang, Lizhen; Mo, Zhongjun; Chen, Wei; Fan, Yubo
Abstract Valgus foot (VF) is the most common foot deformity in children with cerebral palsy (CP), which seriously affects the foot balance in standing and posture control in walking. Little information about the locus and stress of internal bones was available. To accurately describe the biomechanical behavior of the internal bones of VF in CP, we compared the locus and stress of internal bones between the normal foot (NF) and VF by finite element models. Compared with the NF, displacement of the talus and navicular drop in VF increased by 109% and 171% in vertical direction respectively, and the locus of talus had a tendency to clockwise rotation and downward movement in coronal plane. In addition, the abduction angle of forefoot in VF increased up to 10.3°, which was twice more than that in the NF. Moreover, the lateral metatarsophalangeal joints were upward tilted 6.3° comparing with touchdown posture of NF, and peak von Mises stress of the internal bones in VF model concentrated on the fourth metatarsal. The simulation showed that locus of the forefoot, downward rotation of talus head and navicular drop were meaningful to quantify the collapse of medial longitudinal arch. It would provide some suggestions to the rehabilitation treatments of the CP children's VF.